The grammatical category of modality - Hacquard, Valentine (Proceedings of the Amsterdam Colloquium, 2013)
In many languages, the same words are used to express epistemic and root modality. These modals further tend to interact with tense and aspect in systematic ways, based on their interpretation. Is this pattern accidental, or a consequence of grammar or meaning? I address this question by: (i) comparing grammatical modals to verbs/adjectives that share meanings with modals, but not the same scope constraints; (ii) examining patterns of grammaticalization from lexical to grammatical modality; (iii) comparing scope interactions in languages where modals are polysemous and in those where they are not.